School Incivility and Academic Burnout: The Mediating Role of Perceived Peer Support and the Moderating Role of Future Academic Self-Salience - Bai, Qiyu; Liu, Shuang; Kishimoto, Tomoko (Frontiers in Psychology, 2020)
This study examines a mediation model about whether perceived peer support (PPS) mediates the link between school incivility and academic burnout. More importantly, we also investigated how future academic self salience (FASS) as a trait moderates this mediated relationship. We collected data from a sample of 475 students by a two-wave survey. Results indicate that PPS mediated the relationships for school incivility with academic burnout. Moderated mediation analysis further revealed that PPS mediated the relationship for only those students with high FASS, that is, for students who have low future academic self, the relationship between peer support and academic burnout is weaker and not significant. The findings underscore the significance of accounting for individual differences when investigating the relationship between school incivility, PPS and academic burnout